Coconut shell-derived carbon materials via microwave pyrolysis and CO2 activation - Noor Ul Huda Altaf; Muhammad Ayyaz; Lorato Ayalkbet Tekle; Faizan Ahmad; Muhammad Yasin Naz; Yaning Zhang (Biomass and Bioenergy, 2027)

Unveiling the role of heat shock protein 83 (HSP83) in Gossypium hirsutum in enhancing whitefly stress tolerance - Muhammad Waseem Sajjad; Rubab Zahra Naqvi; Ifrah Imran; Mohammad Abubakar Yasin; Mariam Akhtar; Imran Amin (Molecular Genetics and Genomics, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Dual upcycling of waste PET into both the porous support and the Al-MOF filler of thin film nanocomposite nanofiltration membranes - Aroosa Nehal; Aamir Razaq; Asim Laeeq Khan; Muhammad Yasin; Gianluca Viscusi; Giuliana Gorrasi; Mazhar Amjad Gilani; Beenish Shazadi (Journal of Water Process Engineering, 2026)

Machine learning–enhanced framework of complex nonlinear wave dynamics in oceanic atmosphere - Muhammad Qasim; Muhammad Zafarullah Baber; Yakup Yildirim; Adil Jhangeer; Muhammad Waqas Yasin (Ocean Engineering, 2026)

Integration of petrophysical and rock physics analysis to reservoir characterization in the Scarborough Field, Northwest Shelf, Australia - Ahmed Bakry; Qamar Yasin; Ashraf Ghoneimi; Muhammad Nabih (Journal of African Earth Sciences, 2026)

Robust prediction of advanced reservoir petrophysical parameters using conventional logs: Insights from XGB and neural network models - Ahmed Bakry; Ashraf Ghoneimi; Muhammad Nabih; Qamar Yasin; Mohamed Abd Elaziz; Ahmed Elgazar (Marine Geophysical Research, 2026)

Evaluation of anti-diabetic potential of Fagonia indica leaf, seed, and flower extracts via phytochemical profiling, In Vitro, In Silico, and In Vivo approaches - Muhammad Azmat; Muhammad Yasin Ashraf; Naila Ali; Imran Zafar; Ahsanullah Unar; Mohamed Mohany (Phytochemistry Letters, 2026)

Chitosan-crosslinked microwave-engineered biochar alleviates lead stress in Brassica napus by improving soil functioning and plant performance in Pb-contaminated soil - Fakhir Hannan; Yiwa Hu; Ahsan Ayyaz; Muhammad Iqbal; Muhammad Umair Yasin; Iram Batool; Juanjuan Li; Faisal Islam; Yasir Hamid; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Environmental Management, 2026)

Natural Concurrent Infection by Water Moulds of the Genera Achlya and Protoachlya in a Red Tilapia ( Oreochromis sp.) Hatchery in Malaysia - Mohammad Amirul Faiz Zulkiply; Muhammad Salahudin Kheirel Anuar; Mohd Termizi Yusof; Annas Salleh; Ina Salwany Md Yasin; Channarong Rodkhum; Mohammad Noor Amal Azmai (Journal of Fish Diseases, 2026)
This paper reports a natural concurrent infection by water moulds of the genera Achlya and Protoachlya in a red tilapia hatchery in Malaysia. In December 2024, a mass mortality of cultured juvenile red tilapia was noticed at 7 days after transportation and introduction into a hatchery. The affected fish showed lethargy at the bottom of the tanks, loss of appetite, pale colouration, and were isolated from the schooling group. Further examination found brownish cotton wool‐like growth, particularly at the operculum, gills, and at the base of the fins. Several fish exhibited clinical signs including fin rot, gill inflammation, and cloudy eyes. Histopathological examination of the gills revealed secondary lamella necrosis, fusion, hyperplasia, and infiltration of leucocytes. Morphological and molecular identifications revealed the presence of Achlya bisexualis , A. prolifera , and Protoachlya paradoxa in the diseased fish. These organisms belong to the Oomycetes, a group of fungus‐like protists rather than true fungi. Achlya bisexualis and A. prolifera were more sensitive to salinity, with a minimum inhibitory concentration of 15 ppt, compared to P. paradoxa , which was more halotolerant until 25 ppt. The isolated oomycetes demonstrated the ability to grow at temperatures ranging from 5°C to 30°C, with growth rates increasing with temperature. A cumulative mortality rate of 68% with estimated losses of RM 1000 was recorded from the outbreak, while gradual increases in water salinity up to 20 ppt helped to reduce the mortality. Saprolegniasis poses a significant threat to tilapia's egg and fingerling productions in hatchery operations. However, a synergistic multispecies infection of the pathogens may exacerbate the problem.

Detrital zircon geochronology and geochemistry of the Balochistan beach sediments, western Pakistan: Implications for provenance, palaeoweathering, and tectonic setting - Mohammad Naseer; Huan Li; Yasin Rahim; Mohamed Faisal; Yue Hou; Iqtidar Hussain; Shafi Muhammad (Journal of Asian Earth Sciences, 2026)

Integrating Nanotechnology and Bioremediation for Efficient Heavy Metals Removal in Aquatic Ecosystems: A Comprehensive Review - Nadia Yasin; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Muhammad Asrar; Muhammad Mudassar Shahzad; Adan Naeem (Water, Air, & Soil Pollution, 2026)

Integrated Biochar-Based Amendments Enhance Soil Quality and Early Maize Development in Calcareous Soil - Yasin Demir; Halit Tutar; Hasan Er; Azize Doğan Demir; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2026)

Irradiation of hexaploid wheat (Triticum aestivum L.) seeds with varying doses of gamma radiation leads to novel mutants - Nasr Ullah Khan; Bareera Tu Nisa; Ihteram Ullah; Douglas Law; Daniel K. Y. Tan; Wael Elmenofy; Mian Abdur Rehman Arif; Muhammad Yasin (Cereal Research Communications, 2026)
The plateauing wheat yield and its narrow genetic diversity warrants modifying wheat to meet the global food demand from the growing population. Gamma radiation-based mutagenesis is a widely used technique to develop or improve crops like wheat. However, optimizing radiation dose level and the response of wheat genetic background to radiation dose are the two key challenges. This study was conducted to assess the effect of different gamma radiations doses (0 Gy, 100 Gy, 150 Gy, 200 Gy and 250 Gy) on early growth, development and yield related attributes of six wheat genotypes (AZRC Dera, RK2022, landrace-49, landrace-52, black wheat and Kashmiri landrace), and to screen out mutants with promising growth, developmental and yield related attributes. Eighteen different traits (early growth, phenology and yield of the wild type and M 1 mutants) of the six wheat genotypes revealed differences ( p < 0.01) among genotypes (wheat) and treatment (gamma radiation doses), underscoring the genetic diversity and differential radio-sensitivity of the wheat genotypes. Additionally, all the eighteen traits among all genotypes were negatively ( p < 0.01) affected at high dose of 250 Gy, while optimum dose of 150 Gy positively impacted early growth and yield related traits. Kashmiri landrace exhibited improved superior yield related attributes such as early maturity, longer spike, greater spikelets per spike, greater number of seeds per spike and superior seed weight per spike, making it an ideal genetic material for mutation breeding programs. Hierarchical clustering revealed five distinct clusters of genotypes, Kashmir landrace and black wheat being the most distinct genotypes. Gamma radiation mutagenesis produced a vast array of radio morphs such as double spikes per tiller, high tillering, dwarfing and altered spike architecture. These mutants provide novel and valuable genetic resources for wheat breeding.

Comparative evaluation of carbon sequestration and climate change mitigation in commercially planted eucalyptus-based agroforestry systems in a semi-arid region - Ghulam Yasin; Muhammad Azeem Akhter; Muhammad Zubair; Muhammad Talha Imtiaz; Matoor Mohsin Gilani; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Dilnoza Sotiboldiyeva; Shafeeq Ur Rahman (Journal of Environmental Studies and Sciences, 2026)

Mitigating salinity stress in wheat: employing biochemical parameters and stress tolerance index with foliar application of potassium and salicylic acid - Ilker Ugulu; Zafar Iqbal Khan; Farzana Shaheen; Muhammad Yasin Ashraf; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq (Vegetos, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Mechanistic and Synergistic Evaluation of Amodiaquine–Isometamidium Combination Against Trypanosoma evansi: Integrated In Silico–In-Vitro Insights - Waqas Ahmad; Naeem Rasool; Mehmood Ahmad; Muhammad Yasin Tipu; Tehreem Fayyaz; Usama Bin Naeem; Sadaf Aroosa; Rana Muhammad Zahid Mushtaq (Acta Parasitologica, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Biofloc technology: a comprehensive review of its implications for enhancing aquaculture production - Nadia Yasin; Syed Makhdoom Hussain; Bedur Faleh Albalawi; Muhammad Amjad; Adan Naeem; Eman Naeem; Zainab Akram; Mubeena Akbar (Aquaculture International, 2026)

Trichoderma Enhance Soil Properties in Fusarium Infested Soil and Increase Mineral Nutrients of Chickpea Grains: Findings from Field Experiments - Safeer Akbar Chohan; Muhammad Akbar; Muhammad Asad Farooq; Nasim Ahmad Yasin; Umer Iqbal; Tayyaba Khalil (Journal of Soil Science and Plant Nutrition, 2026)

Influence of functional diversity on aboveground biomass accumulation in subtropical sub montane forests - Muhammad Majeed; Akash Jamil; Yongheng Gao; Ghulam Yasin; Umair Younas; Elena Pismennaya; Ksenia Myachina; Nasir Qadir (Journal of Mountain Science, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal dynamics of a reaction-diffusion nutrient-algae model - Muhammad Waqas Yasin; Mobeen Akhtar; Moutaz Alazab; Mustafa Inc; Zafarullah Baber; Muhammad Sajid Iqbal; Shahram Rezapour (Modeling Earth Systems and Environment, 2026)

The whitefly Bemisia tabaci transmits the Pepper yellow leaf curl Indonesia virus to chili plants treated with low-risk insecticides - Ernawati Djaya; Iftitah Kartika Amaliah; Nurul Arfiani; Melina Melina; Erwin Najamuddin; Nurasiah Djaenuddin; Amran Muis; Ramlah Arief; Muhammad Yasin; Andi Nasruddin (Crop Protection, 2026)

Communication-aware multi-agent reinforcement learning for cooperative navigation of multiple USVs in dynamic ocean environments - Umar Draz; Sana Yasin; Tariq Ali; Mohammad Hijji; Muhammad Ayaz; El-Hadi M . Aggoune (Ocean Engineering, 2026)

Succinic acid enhances sedative activity of diazepam through GABAergic receptor modulation: Evidence from behavioral approach and computational insights - Md. Sakib Al Hasan; Yasin Emon; Mohammad Y. Alshahrani; Imam Hossen Rakib; Emon Mia; Abida Sultana; Akayed Hasan; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Reimagining human creativity and learning in the age of generative AI: A multi-method meta-thematic synthesis - Muhammad Bilal Zafar; Hassnian Ali; Talha Yasin (Next Research, 2025)

Switching on survival: how rice outsmarts heat with a natural gene circuit - Mohammad Abubakar Yasin; Muhammad Waseem Sajjad; Rubab Zahra Naqvi; Imran Amin; Muhammad Arif (Functional & Integrative Genomics, 2025)

Depositional age and provenance of the Maziping Group, South China: Evidence from detrital zircon U–Pb dating and whole-rock geochemistry - Yasin Rahim; Huan Li; Thomas J. Algeo; Weidong Ren; Annan Guan; Mohammad Naseer; Zaheen Ullah; Asad Khan; Muhammad Yaseen; Mohamed Faisal (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Paleoenvironmental conditions and key drivers of organic matter accumulation in the early cretaceous Talhar Shale, Lower Indus Basin, Pakistan - Rizwan Sarwar Awan; Bo Liu; Qamar Yasin; David A. Wood; Hamad ur Rahim; Muhammad Amar Gul; Sajjad Ali; Khawaja Hasnain Iltaf; Ashar Khan (Journal of Asian Earth Sciences, 2025)

Oral adjuvanted Vibrio vaccine enhances antibody production and lysozyme activity in the serum and mucus of marine-cultured red hybrid tilapia (Oreochromis sp.) against V. harveyi and V. alginolyticus - Tilusha Manchanayake; Aslah Mohamad; Zahaludin Amir-Danial; Nadirah Abu Nor; Chin Yong-Kit; Muhammad Farhan Nazarudin; Roslindawani Md Nor; Qistina Hasnan; Mohd Zamri-Saad; Mohammad Noor Azmai Amal; Md Yasin Ina-Salwany; Annas Salleh (Fish & Shellfish Immunology, 2025)

Designing MgAlCe-Adenine LDH@g-C3N4 nanohybrid integrated polypropylene for bi-functional flame retardancy and corrosion protection - Salman Khalid; Jun Sun; Xinyu Chen; Mohammad Tabish; Mubashar Mahmood; Muhammad Mubeen; Yangming Zou; Zhenhua Wang; Xiaoyu Gu; Jingmao Zhao; Ghulam Yasin; Sheng Zhang (Chemical Engineering Journal, 2025)

Bifurcation analysis and turing instability of the ecological model having Beddington–Deangelis-type functional response - Muhammad Waqas Yasin; Nauman Ahmed; Ali Akgül; Muhammad Zafarullah Baber; Fengping Yao (Modeling Earth Systems and Environment, 2025)

A systematic review on the development and efficacy of nano-based vaccine in aquaculture - Shamsu Ibrahim Ishaq; Muhammad Salahudin Kheirel Anuar; Abdulwakil Olawale Saba; Ina Salwany Md Yasin; Che Azurahanim Che Abdullah; Annas Salleh; Muhammad Farhan Nazarudin; Mohd Termizi Yusof; Mohammad Noor Amal Azmai (Aquaculture International, 2025)

Nano-engineered biochar enhances soil microbial interactions and maize transcriptomic pathways for cadmium detoxification - Muhammad Umair Yasin; Sajid Muhammad; Nana Chen; Fakhir Hannan; Muhammad Afzal; Zulqarnain Haider; Bahar Ali; Irshan Ahmad; Muhammad Rehman; Yinbo Gan (Journal of Hazardous Materials, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Polyethylene Glycol Mitigates Cadmium Toxicity in Raphanus sativus L. by Regulating Enzymatic and Nonenzymatic Antioxidant Defence Mechanisms - Muhammad Sajid; Shakil Ahmed; Rehana Sardar; Nasim Ahmad Yasin (Journal of Soil Science and Plant Nutrition, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Quantitative assessment of asymptomatic spinal cord compression using MRI: a multi-center study - Ali F. Khan; Sanaa Hameed; Alaa Baha; Fauziyya Muhammad; Grace Haynes; Amber Dastgir; Suresh K. Gulla; Hakeem J. Shakir; Michael L. Rohan; Yasin Y. Dhaher; Zachary A. Smith (GeroScience, 2025)

Impact Assessment of Optimal Water Allocation Using a Linear Model in Lower Bari Doab Canal Command Area - Atiqa Yasin; Muhammad Awais Zafar; Muhammad Masood; Ghulam Nabi; Mudassar Iqbal (Water Conservation Science and Engineering, 2025)

Exploring the fixed point theory and numerical modeling of fish harvesting system with Allee effect - Muhammad Waqas Yasin; Mobeen Akhtar; Nauman Ahmed; Ali Akgül; Qasem Al-Mdallal (Modeling Earth Systems and Environment, 2025)

Adaptive responses of trees to industrial pollution: modulation of leaf anatomical, physio-biochemical, and heavy metal accumulation traits in urban biotopes - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Mansoor Javaid; Usman Zulfiqar; Nafosat Djonibekova; Anarjan Matkarimova; Hesham S. Almoallim; Mohammad Javed; Shafeeq Ur Rahman (Environmental Monitoring and Assessment, 2025)

Synthesis and optimization of silver-modified BiOCl/CuBi2O4 heterostructure composite as an efficient visible light photocatalyst against reactive green 5 and turquoise blue dyes - Raheeba Akbar; Haq Nawaz Bhatti; Muhammad Zahid; Muhammad Yasin Naz (Environmental Science and Pollution Research, 2025)

When low-dimensional nanomaterials meet polymers: A promising configuration for flame retardancy and corrosion protection - Salman Khalid; Muhammad Mubeen; Mohammad Tabish; Muhammad Jawad; Muhammad Uzair Malik; H.M. Ahsen Ilyas; Mubashar Mahmood; Mohammed Mujahid Alam; Jun Sun; Ghulam Yasin (Chemical Engineering Journal, 2025)

Review of single-atom electrocatalysts for hydrogen and oxygen evolution reactions from water-splitting - Muhammad Shoaib; Muhammad Yasin Naz; Tong Wu; Hafeez Ur Rehman; Enqi Sun; Aiping Li; Qiliang Zhu; Ning Wang (Fuel, 2025)

Talaromyces purpureogenus-mediated mycosynthesis of aluminium oxide nanoparticles and characterization of the physicochemical properties at different calcination temperatures - Muhammad Salahudin Kheirel Anuar; Che Azurahanim Che Abdullah; Muhammad Farhan Nazarudin; Shamsu Ibrahim Ishaq; Mohammad Noor Amal Azmai; Annas Salleh; Ina Salwany Md Yasin; Mohd Termizi Yusof (Fungal Biology, 2025)

Pharmacological Potential of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835): Antibacterial Activity Against Methicillin-Resistant Staphylococcus aureus and Metabolite Profile - Abdoulie Ceesay; Muhammad Farhan Nazarudin; Norfarrah Mohamed Alipiah; Ina Salwany Md Yasin; Mohammad Noor Azmai Amal; Mohamad Azzam Mohd Sayuti; Intan Safinar Ismail; Mohammed Aliyu-Paiko (Thalassas: An International Journal of Marine Sciences, 2025)

Spatio-temporal patterns and Turing–Hopf bifurcation in a spatially extended prey–predator model with ratio-dependent interactions - Muhammad Waqas Yasin; Nauman Ahmed; Ali Akgül; Muhammad Zafarullah Baber; Dumitru Baleanu; Ovidiu Tintareanu-Mircea (Modeling Earth Systems and Environment, 2025)

Exploitation of genetic variation to enhance grain nutrient contents in bread wheat through conventional and molecular approaches - Rabia Ikram; Sania Begum; Nasr Ullah Khan; Muhammad Mohibullah; Muhammad Shakeel; Salma Shaheen; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Iram Ijaz; Muhammad Yasin (Cereal Research Communications, 2025)

Innovative early age mechanical properties of 3D printable mortar enhanced with SBR latex and kaolin - Mazhar Yasin; Zahid Ahmad Siddiqi; Atteq Ur Rehman; Sadaf Noshin; Hafiz Muhammad Shahzad Aslam (European Journal of Environmental and Civil Engineering, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

In-Situ Self-Transformation Growth of Binary g-C3N4/CdS Heterojunctions for Efficient Hydrogen Evolution and Wastewater Treatment - Muhammad Irfan; Muhammad Shoaib; Humaira Hussain; Muhammad Yasin Naz; Shazia Shukrullah; Saifur Rahman; Salim Nasar Faraj Mursal; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2025)

Insight into polyethylene glycol-mediated physiochemical, nutritional, and antioxidative defense modulations in salt-stressed Raphanus sativus L - Muhammad Sajid; Shakil Ahmed; Rehana Sardar; Nasim Ahmad Yasin (Physiology and Molecular Biology of Plants, 2025)

Association mapping of leaf rust disease resistance and yield related traits in bread wheat using a high density 90K SNP array - Muhammad Rauf Shah; Muhammad Ali Sher; Salma Bashir; Muhammad Zeshan Zafer; Douglas Law; Sania Begum; Nasr Ullah Khan; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Daniel K. Y. Tan; Muhammad Yasin (Journal of Plant Diseases and Protection, 2025)

Correction to: Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-Ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Effect of resveratrol on post-thaw motility, kinematics, structural parameters and antioxidant/oxidant status of Kamori buck spermatozoa - Tarique Hussain; Muhammad Hammad Fayyaz; Amjad Hameed; Syed Murtaz Hassan Andrabi; Rehana Kausar; Yasin Mubashir; Iqra Batool; Muhammad Shahzad; Ali Dogan Omur (Cryobiology, 2025)

Microwave-assisted pyrolysis of biomass: Influence of feedstock and pyrolysis parameters on porous biochar properties - Tianhao Qiu; Chengxiang Li; Wenke Zhao; Muhammad Yasin Naz; Yaning Zhang (Biomass and Bioenergy, 2025)

Regulatory mechanisms of trichome and root hair development in Arabidopsis - Muhammad Umair Yasin; Yihua Liu; Minjie Wu; Nana Chen; Yinbo Gan (Plant Molecular Biology, 2025)

Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Iram Ijaz; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Dual-strategy approach for Rhynchophorus ferrugineus control: Endophytic Beauveria bassiana and Bacillus thuringiensis topical application - Muhammad Yasin; Waqas Wakil; Nickolas G. Kavallieratos; Nikoleta Eleftheriadou; Aqsa Naeem; Mirza Abdul Qayyum; Muhammad Asrar; Saleh S. Alhewairini; David Shapiro-Ilan (Crop Protection, 2025)

Elucidation of synbiotic diet comprising of Lactobacillus plantarum L20 and Sargassum polycystum on gastrointestinal microbiota, tissue structures and AHPND associated dysbiosis susceptibility in black tiger shrimp (Penaeus monodon) - Yong Kit Chin; Mohamad Azzam-Sayuti; Aslah Mohamad; Wan Omar Haifa-Haryani; Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Nur Shidaa Mohd Ali; Md Yasin Ida-Muryany; Murni Marlina Abd Karim; Salleh Annas; Mohd Nor Norhariani; Mohammad Noor Azmai Amal; et al. (Aquaculture, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

A systematic investigation of multi-attributive border approximation area comparison approach with Gaussian membership function for optimizing water quality - Yasir Yasin; Gulay Demir; Muhammad Riaz; Muhammad Aslam; Dragan Pamucar (Environment, Development and Sustainability, 2024)

Bioderived carbon quantum dots boost maize growth and photosynthesis by augmenting UV spectrum absorption and carbon assimilation regulatory genes - Zulqarnain Haider; Chunyan Yang; Irshan Ahmad; Samta Zia; Muhammad Haseeb Javaid; Muhammad Rehman; Muhammad Umair Yasin; Bahar Ali; Chen Nana; Yinbo Gan (Journal of Environmental Chemical Engineering, 2024)

Advancements in sustainable production of biofuel by microalgae: Recent insights and future directions - Muhammad Abdullah; Zain Ali; Muhammad Talha Yasin; Kinza Amanat; Fatima Sarwar; Jallat Khan; Khurshid Ahmad (Environmental Research, 2024)

Successful application of modified crude DNA extraction from muscle tissues for various types of PCR amplifications - Sana Jafar; Salman Jamil; Muhammad Sheraz Yasin; Asif Naseem; Muhammad Yasir Zahoor; Wasim Shehzad; Muhammad Imran (Molecular Biology Reports, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Nanobiochar-Coating Regulates N and P Release from DAP Fertilizer in Soil and Improves Maize Crop Productivity - Ghulam Abbas Shah; Mughees Mustafa; Hani Z. Asfour; Khubra Shoukat; Ahsan Yasin; Nadeem Ali; Muhammad Bilal Khan Niazi; Gabrijel Ondrasek; Muhammad Imtiaz Rashid (Journal of Soil Science and Plant Nutrition, 2024)

Heterostructured melamine resin Spheres@GO reinforced epoxy composite achieving robust Corrosion-Resistance of Zn-Al-Mg coated steel for automotive applications - Muhammad Mubeen; Jingmao Zhao; Mohammad Tabish; Jingbao Wang; Mubashar Mahmood; Hassan Murtaza; Muhammad Jawad; Baomin Fan; Ghulam Yasin (Chemical Engineering Journal, 2024)

Low doses of entomopathogens matter hugely, gateway to resistance development and retarded growth in Helicoverpa armigera - Mirza Abdul Qayyum; Zhuo Zhihang; Waqas Wakil; Habib Ali; Abid Ali; Muhammad Usman Ghazanfar; Muhammad Yasin; Xu Danping; Hasham S. Almoallim; Mohammad Javed Ansari; Muhammad Tahir; Kashif Ali; et al. (Journal of Plant Diseases and Protection, 2024)

Legume choice and planting configuration influence intercrop nutrient and yield gains through complementarity and selection effects in legume-based wheat intercropping systems - Muhammad Ali Raza; Atta Mohi Ud Din; Ghulam Abbas Shah; Wang Zhiqi; Ling Yang Feng; Hina Gul; Hassan Shehryar Yasin; Mohammad Shafiq ur Rahman; Chen Juan; Xue Liang; Raheela Rehman; Amal Mohamed Al Garawi; et al. (Agricultural Systems, 2024)

Effect of zinc fortified, arid and irrigated wheat varieties flour upon life history parameters of red flour beetle, Tribolium castaneum (Herbest) (Coleoptera: Tenebrionidae) - Muhammad Rizwan; Muhammad Yasin; Muhammad Tahir; Ammad Ahmad; Ansa Banazeer; Muhammad Babar Shahzad Afzal; Umair Sagheer (Journal of Stored Products Research, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Identification of Four Novel Candidate Genes for Non-syndromic Intellectual Disability in Pakistani Families - Iftikhar Ahmed; Muhammad Muzammal; Muzammil Ahmad Khan; Hafiz Ullah; Arshad Farid; Muhammad Yasin; Jabbar Khan; Khurshid Alam; Asif Mir (Biochemical Genetics, 2024)

In vivo assessment of Lactobacillus plantarum strains in black tiger shrimp (Penaeus monodon): implications for growth performance, probiotic-pathogen interaction, and defense against AHPND infection - Yong Kit Chin; Wan Omar Haifa-Haryani; Muhammad Farhan Nazarudin; Mohd Ihsanuddin Ahmad; Mohamad Azzam-Sayuti; Nur Shidda Mohd Ali; Mohamad Syazwan Ngalimat; Aslah Mohamad; Md Yasin Ida-Muryany; Murni Karim; Annas Salleh; Mohd Nor Norhariani; et al. (Aquaculture International, 2024)

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

A sustainable bioprocessing system leveraging gas fermentation and bipolar membrane electrodialysis system for direct recovery of acetic acid - Mungyu Lee; Jae-Hun Kim; Muhammad Yasin; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2024)

Survival, immune response and growth of Penaeid shrimp as affected by immunostimulants: A meta-analysis - Muhammad Ismunandar Yasin Saleh; Sukenda; Widanarni; Anuraga Jayanegara (Fish & Shellfish Immunology, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

Supplementation of nano-biochar improved growth and physiological attributes in wheat seedlings exposed to salt stress through enhanced activity of hydrolysing and nitrogen metabolic enzymes and regulation of crucial metabolites - Waqas Yousaf; Anis Ali Shah; Muhammad Bilal Afzal; Zaib-un Nisa; Naila Ali; Muhammad Yasin Ashraf; Hosam O. Elansary; Aqeel Ahmad (South African Journal of Botany, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Organic waste-to-bioplastics: Conversion with eco-friendly technologies and approaches for sustainable environment - Zain Ali; Muhammad Abdullah; Muhammad Talha Yasin; Kinza Amanat; Khurshid Ahmad; Ishfaq Ahmed; Muther Mansoor Qaisrani; Jallat Khan (Environmental Research, 2024)

Interactive mode of biochar-based silicon and iron nanoparticles mitigated Cd-toxicity in maize - Muhammad Umair Yasin; Fakhir Hannan; Raheel Munir; Sajid Muhammad; Muhammad Iqbal; Iqra Yasin; Muhammad Saad Shoaib Khan; Farah Kanwal; Yang Chunyan; Xingming Fan; Yinbo Gan (Science of The Total Environment, 2024)

Effect of experimental boundary conditions and treatment-time on the electro-desalination of soils - Abdul Ahad Hussain; Kashif Kamran; Muhammad Imran; Aasma Akram; Lin Li; Maryam Hina; Muhammad Yasin Naz; Muhammad Shabir Mahr; Athar Mahmood; Abdallah A. A. Mohammed (Environmental Geochemistry and Health, 2024)

Potential of two entomopathogenic fungi, Beauveria bassiana and metarhizium anisopliae as biocontrol agents of Rhpalosiphum padi and Shizaphis graminum, (Homoptera: Aphididae) in laboratory and field - Misbah Ashraf; Dilbar Hussain; Shahbaz Hussain; Naima Din; Qurban Ali; Muhammad Shah Jahan; Muhammad Yasin; Muhammad Farooq (International Journal of Tropical Insect Science, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Advances/Scope and prospects of g-C3N4 derived fascinating photocatalyst as a leading route towards solar energy adaption - Asif Hayat; Muhammad Sohail; Zeeshan Ajmal; Hala H. Abd El-Gawad; Djamel Ghernaout; Yas Al-Hadeethi; Saleem Raza; Yasin Orooji (Journal of Cleaner Production, 2024)

Bacterial inoculation remediates heavy metals toxicity through modulating biochemicals and antioxidant enzymes of Daucus carota L. grown in lead contaminated soil - Naima Huma Naveed; Naveed Abbas Nasir; Anis Ali Shah; Tahir Shahzad; Nasim Ahmad Yasin; Zain Ali; Muhammad Jamil; Talha Javed; Aamir Ali (South African Journal of Botany, 2023)

Effect of crop combination on yield performance, nutrient uptake, and land use advantage of cereal/legume intercropping systems - Muhammad Ali Raza; Wang Zhiqi; Hassan Shehryar Yasin; Hina Gul; Ruijun Qin; Sana Ur Rehman; Aqib Mahmood; Zafar Iqbal; Zaheer Ahmed; Shuanglong Luo; Chen Juan; Xue Liang; et al. (Field Crops Research, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Sustainable remediation of dye-contaminated wastewater using novel cross-linked Hex-CCP-co-PPT microspheres - Sahid Mehmood; Fazal Haq; Mehwish Kiran; Ibrahim A. Shaaban; Mohammed A. Assiri; Muhammad Haroon; Muhammad Yasin; Arshad Farid; Alam Nawaz; Majid Majeed Akbar; Zeinhom M. El-Bahy (Chemosphere, 2023)

Estimating hardness and Young's modulus of shale using drill cuttings: Implications for hydraulic fracturing in shale gas reservoir development - Ghulam Mohyuddin Sohail; Qamar Yasin; Ahmed E. Radwan; Muhammad Zaka Emad (Gas Science and Engineering, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Acetogen and acetogenesis for biological syngas valorization - Ji-Yeon Kim; Mungyu Lee; Soyoung Oh; Byeongchan Kang; Muhammad Yasin; In Seop Chang (Bioresource Technology, 2023)

Transforming Bombax ceiba L. sawdust waste into a valuable growth substrate: An example with sugarcane - Muhammad Yasin; Muhammad Usman Zia; Athar Mahmood; Muhammad Mansoor Javaid; Muhammad Ather Nadeem; Christian Andreasen (Bioresource Technology Reports, 2023)

Photocatalytic and Antibacterial Potential of Chitosan Supported Nickel Oxide/Zinc Oxide Composite Synthesized by Alcohothermal Method - Amna Yasin; Tousif Hussain; Riaz Ahmad; Urooj Shuaib; Muhammad Amjad; Sajjad Ahmad; M. Imranullah (Water, Air, & Soil Pollution, 2023)

Vector indices and metrological factors associated with dengue fever outbreak in Punjab, Pakistan - Muhammad Irfan Akram; Waseem Akram; Muhammad Asif Qayyoum; Adeela Anwar Rana; Muhammad Yasin; Bushra Saddiq (Environment, Development and Sustainability, 2023)

Testing of Magnetic ZnO/MgFe2O4 Heterostructures for Photocatalytic Removal of Synthetic Dye Pollutants from Wastewater - Muhammad Shoaib; Muhammad Adnan Munir; Muhammad Yasin Naz; Ghulam Abbas; Muhammad Irfan; Saifur Rahman; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2023)

Composted Melia azedarach L. (Chinaberry tree) Sawdust Mixtures Regulate the Sprouting and Growth of Single Bud Node Seedlings of Sugarcane - Mehwish Sultan Ahmed; Muhammad Yasin; Muhammad Usman Zia; Muhammad Ather Nadeem; Sher Muhammad; Athar Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Application of silicon and sodium hydrosulfide alleviates arsenic toxicity by regulating the physio-biochemical and molecular mechanisms of Zea mays - Aishah Alatawi; Manar Fawzi Bani Mfarrej; Rana M. Alshegaihi; Muhammad Ahsan Asghar; Sahar Mumtaz; Ghulam Yasin; Romina Alina Marc; Shah Fahad; Mohsen Mohamed Elsharkawy; Sadia Javed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Abundance and Distribution of Macro- and Mesoplastic Debris on Selected Beaches in the Northern Strait of Malacca - Er Vin Lim; Nithiyaa Nilamani; Norhanis M. Razalli; Shoufeng Zhang; Hongjun Li; Muhammad Lutfi Haron; Anisah Lee Abdullah; Zulfigar Yasin; Norlaila Mohd Zanuri; Aileen Tan Shau Hwai (Journal of Marine Science and Engineering, 2023)
Plastics account for 60–80% of marine debris worldwide, and, in 2021, Malaysia was the 28th largest plastic polluter in the world. In light of this finding, the Malaysian government has launched the Roadmap Towards Zero Single-Use Plastics 2018–2030 and the Plastics Sustainability Roadmap 2021–2030 to reduce plastic pollution and implement a circular economy for Malaysia. A comprehensive database of the status of plastic pollution in Malaysia is needed to achieve this target. This study aims to record the presence of macro- (>2.5 cm) and mesoplastic (0.5–2.5 cm) debris at selected beaches in the northern Strait of Malacca. All study sites are publicly accessible beaches (Pulau Songsong, Teluk Aling, and Pulau Gazumbo) except Pulau Lembu, which is in a Marine Protected Area (MPA). The debris was collected from predetermined transects on the beach and categorised according to its form and economic market segments in Malaysia. Most of the macro- (53–75% of total mass) and mesoplastics (52–80% of the total number) were accumulated in the backshore area. Public beaches such as Pulau Gazumbo and Pulau Songsong recorded the highest abundance of macroplastics, with 7.32 g/m2 and 9.77 g/m2, respectively. Teluk Aling recorded the lowest abundance of macroplastics (3.58 g/m2) but the highest in mesoplastics (0.55 items/m2). Most of the macroplastics found were packaging plastics such as plastic bottles, containers, and polystyrene foam debris. Although Pulau Lembu is an MPA, the amount of macroplastics found was considerably high (7.17 g/m2). Based on the beach cleanliness index, Pulau Gazumbo (−3.99) was the dirtiest site, followed by Pulau Lembu (−2.92) and Pulau Songsong (−2.85), while Teluk Aling (−1.63) was the cleanest site, which can explain the amount of macroplastic debris found. However, all the study sites’ cleanliness may not be ideal, as the indexes were less than zero due to the low availability of waste bins and insufficient frequency of beach cleaning. This may not be able to curb the effects of high anthropogenic activities conducted in addition to uncontrollable natural factors.

Farm households' perception and adaptation to climate change in relation of food crop productivity in Pakistan - Seher Muneer; Khuda Bakhsh; Rafaqet Ali; Muhammad Asim Yasin; Muhammad Asif Kamran (Environment, Development and Sustainability, 2023)

Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery - Naila Amin; Muhammad Aslam; Zakir khan; Muhammad Yasin; Shakhawat Hossain; Muhammad Kashif Shahid; Abrar Inayat; Ahmed Samir; Rizwan Ahmad; Mohammad N. Murshed; Muhammad Shahzad Khurram; Mohamed E. El Sayed; et al. (Chemosphere, 2023)

Macroalgal biochar synthesis and its implication on membrane fouling mitigation in fluidized bed membrane bioreactor for wastewater treatment - Muhammad Maaz; Muhammad Aslam; Muhammad Yasin; Asim Laeeq Khan; Azeem Mushtaq; Tahir Fazal; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Jeonghwan Kim (Chemosphere, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Diversity of hipparionines (Perissodactyla: Equidae) from the late Miocene–Pliocene Siwalik deposits at Haritalyangar, India - Anek Ram Sankhyan; Sayyed Ghyour Abbas; Muhammad Akbar Khan; Muhammad Adeeb Babar; Amir Yasin (Annales de Paléontologie, 2023)

Impact of eco-friendly chemical pretreatment on physicochemical and surface mechanical properties of sustainable lignocellulosic agricultural waste - Muhammad Sulaiman; Fahad Ali Rabbani; Tanveer Iqbal; Mohsin Ali Kazmi; Saima Yasin; M.A. Mujtaba; M.A. Kalam; Fares Almomani (Algal Research, 2023)

Seismic stratigraphy and attributes application for imaging a Lower Cretaceous deltaic system: Sukkur rift zone, Lower Indus Basin, Pakistan - Perveiz Khalid; Asam Farid; Muhammad Tayyab Naseer; Qamar Yasin; Shazia Naseem (Marine and Petroleum Geology, 2023)

Algae extract delamination of molybdenum disulfide and surface modification with glycidyl methacrylate and polyaniline for the elimination of metal ions from wastewater - Saleem Raza; Muhammad Usman Hameed; Ehsan Ghasali; Asif Hayat; Yasin Orooji; Hongjun Lin; Ceren Karaman; Fatemeh Karimi; Nevin Erk (Environmental Research, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

Deep learning-based marine big data fusion for ocean environment monitoring: Towards shape optimization and salient objects detection - Sulaiman Khan; Inam Ullah; Farhad Ali; Muhammad Shafiq; Yazeed Yasin Ghadi; Taejoon Kim (Frontiers in Marine Science, 2023)
Objective During the last few years, underwater object detection and marine resource utilization have gained significant attention from researchers and become active research hotspots in underwater image processing and analysis domains. This research study presents a data fusion-based method for underwater salient object detection and ocean environment monitoring by utilizing a deep model. Methodology A hybrid model consists of an upgraded AlexNet with Inception v-4 for salient object detection and ocean environment monitoring. For the categorization of spatial data, AlexNet is utilized, whereas Inception V-4 is employed for temporal data (environment monitoring). Moreover, we used preprocessing techniques before the classification task for underwater image enhancement, segmentation, noise and fog removal, restoration, and color constancy. Conclusion The Real-Time Underwater Image Enhancement (RUIE) dataset and the Marine Underwater Environment Database (MUED) dataset are used in this research project’s data fusion and experimental activities, respectively. Root mean square error (RMSE), computing usage, and accuracy are used to construct the model’s simulation results. The suggested model’s relevance form optimization and conspicuous item prediction issues in the seas is illustrated by the greatest accuracy of 95.7% and low RMSE value of 49 when compared to other baseline models.

Construction of microbial electrodialysis cells equipped with internal proton migration pathways: Enhancement of wastewater treatment, desalination, and hydrogen production - Mohd Nur Ikhmal Salehmin; Muhammad Farhan Hil Me; Wan Ramli Wan Daud; Nazlina Haiza Mohd Yasin; Mimi Hani Abu Bakar; Abu Bakar Sulong; Swee Su Lim (Science of The Total Environment, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Combinations of Beauveria bassiana and spinetoram for the management of four important stored-product pests: laboratory and field trials - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Mirza Abdul Qayyum; Taha Yaseen; Muhammad Usman Ghazanfar; Muhammad Yasin (Environmental Science and Pollution Research, 2022)
The current study examines the efficacy of the semi-synthetic insecticide spinetoram and entomopathogenic fungi Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae) as wheat protectants against the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), and the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), under laboratory and field trials. One dose of B. bassiana , i.e., 1 × 10 7 conidia/kg wheat, two doses of spinetoram, i.e., spine1: 0.05 ppm (mg/kg wheat), spine2: 0.1 ppm, and their combinations (Bb + spine1, Bb + spine2) were evaluated at 20, 25, and 30 °C. All treatments provided significantly higher mortality at 30 °C compared with the other two temperatures. Maximum mortality levels were observed in the treatments where B. bassiana was combined with the higher dose of spinetoram (0.1 ppm). All treatments reduced progeny production in comparison with the control groups. Maximum progeny reduction was observed at 30 °C, on wheat treated with the Bb + spine2 combination. The combination Bb + spine2 also provided elevated mortality rates in both laboratory and field persistence trials, but at 180 days caused moderate mortality to all tested insect species. Concerning progeny, at laboratory persistence trials, the combination Bb + spine2 exhibited the lowest offspring emergence to all tested species compared to the other treatments and control. Overall, our study showed that R. dominica was the most susceptible species followed by S. granarius , T. castaneum , and T. granarium . Our findings revealed that the combination of B. bassiana and spinetoram may be a useful tool for efficient and advanced integrated pest management strategies for long storage periods under multiple temperatures.

Determinants of risk attitude and risk perception under changing climate among farmers in Punjab, Pakistan - Muhammad Farhan; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Sami Ullah; Saad Munir (Natural Hazards, 2022)

An analysis of the environmental impacts of ethnic diversity, financial development, economic growth, urbanization, and energy consumption: fresh evidence from less-developed countries - Iftikhar Yasin; Sana Naseem; Muhammad Awais Anwar; Ghulam Rasool Madni; Haider Mahmood; Muntasir Murshed (Environmental Science and Pollution Research, 2022)

Thiourea Application Improves the Growth and Seed and Oil Yields in Canola by Modulating Gas Exchange, Antioxidant Defense, and Osmoprotection Under Heat Stress - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Saddam Hussain; Muhammad Umair Yasin; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Development of early flowering, short life-spanned jute (Corchorus spp.) mutant via ethyl methane sulfonate mutagenesis - Quazi Md. Mosaddeque Hossen; S. M. Badier Rahman; Md. Nazibur Rahman; Muhammad Delwar Hossain Sarker; Md. Moniruzzaman; Md. Zablul Tareq; Md. Abu Sadat; Kazi Md. Yasin Arafat; Md. Sarwar Jahan; Md. Samiul Haque (Journal of Crop Science and Biotechnology, 2022)

Determination and detoxification of aflatoxin and ochratoxin in maize from different regions of Pakistan - Syed Wajih ul Hassan Shah Gillani; Yumna Sadef; Muhammad Imran; Hafiz Muhammad Fahad Raza; Aamir Ghani; Sumera Anwar; Muhammad Yasin Ashraf; Shabbir Hussain (Environmental Monitoring and Assessment, 2022)

Nutritional compositions, pathogenic microorganisms and heavy metal concentration in green turtle eggs (Chelonia mydas) from Terengganu and Sabah, Malaysia - Nor Hashikin Katni; Amirul Faiz Mohd Azmi; Maizah Mohd Abdullah; Mohd Uzair Rusli; Zunita Zakaria; Tengku Rinalfi Putra Tengku Azizan; Azlan Che’ Amat; Mohd Zamri Saad; Ina Salwany Md. Yasin; Muhammad Farhan Nazarudin; Hasliza Abu Hassim (Frontiers in Marine Science, 2022)
A total of 60 green turtle eggs were obtained from sampling sites in Terengganu and Sabah, Malaysia. Isolation and identification of bacteria from these eggs resulted in 12 genera of Gram-negative bacteria with 12 different species. The most frequently isolated bacteria were Salmonella (30.9%) and Proteus (23.7%). The rest of the microorganisms were Aeromonas, Escherichia, Citrobacter, Enterobacter, Klebsiella, Morganella, Pseudomonas, Shigella, Serratia and Photobacterium. A slight difference in total crude protein content was recorded in the samples from Terengganu and Sabah, at 16.3% Dry matter (DM) and 15.8% DM, respectively. Meanwhile, the crude fat content found in the samples from Terengganu was 9.88% DM and 7.79% DM from Sabah. In this study, α-linolenic acid, C18:3 n-3 (Terengganu: 16.87% DM) and linoleic acid, C18:2 n-6 (Sabah: 15.19% DM) were the most prevalent fatty acids in both samples. The green turtle egg samples from Terengganu showed higher value of total saturated fatty acid, total C18:3 n-3 and C18:2 n-6 and total polyunsaturated fatty acids as compared to green turtle eggs from Sabah. The results also revealed that majority of the essential amino acids (EAA) recorded in samples from both sampling sites was lysine (9.67% DM), with higher value recorded in green turtle egg from Terengganu. However, there were no significant differences ( p >0.05) in the nutritional compositions, fatty acid contents and amino acid compositions of the samples between the two sampling sites. Meanwhile, statistical analysis showed significant differences in heavy metal concentrations between the two sampling sites for all the six heavy metals detected in this study (Hg, Cd, Pb, Mn, Zn and Cu). The ranking of heavy metals concentration in turtle eggs from both sampling sites, in decreasing order is as follows: Zn > Cu > Mn > Pb > Cd > Hg. Overall, these results reveal the contents and contaminations of a green turtle egg, which may raise concern on public health risks. Findings from this study will also be beneficial for the future conservation of green turtle population when the consumption of their eggs should be stopped.

Uncovering the role of melatonin in plant stress tolerance - Ahsan Ayyaz; Aneela Kanwal Shahzadi; Saba Fatima; Ghulam Yasin; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Muhammad Ahsan Farooq (Theoretical and Experimental Plant Physiology, 2022)

Assessment of Malaysian brown seaweed Padina gymnospora antioxidant properties and antimicrobial activity in different solvent extractions - Muhammad Farhan Nazarudin; Muhammad Syazwan Shahidan; Nur Amirah Izyan Noor Mazli; Tan Hui Teng; Yam Sim Khaw; Ina Salwany Md Yasin; Azizul Isha; Mohammed Aliyu-Paiko (Fisheries Science, 2022)

Do Agriculture Technologies Influence Carbon Emissions in Pakistan? Evidence based on ARDL technique - Rafaqet Ali; Rabia Ishaq; Khuda Bakhsh; Muhammad Asim Yasin (Environmental Science and Pollution Research, 2022)

Strengthening of high plastic clays by geotextile reinforcement - Muhammad Hamza; Mubashir Aziz; Wang Xiang; Muhammad Waqas Younis; Zhihong Nie; Muhammad Ali; Mudassar Dilawar; Ashiru Mohammed; Farhad Ali; Rahat Ullah; Mazhar Yasin; Atteq Ur Rehman (Arabian Journal of Geosciences, 2022)

Antimicrobial Resistance of Shigella flexneri in Pakistani Pediatric Population Reveals an Increased Trend of Third-Generation Cephalosporin Resistance - Iqbal Nisa; Mohammad Haroon; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Nusrat Yasin; Mubashir Hussain; Taj Ali Khan; Amjad Ali; Saeed Ahmad Khan; Muhammad Qasim (Current Microbiology, 2022)

Climate change impact uncertainty assessment and adaptations for sustainable maize production using multi-crop and climate models - Mubashra Yasin; Ashfaq Ahmad; Tasneem Khaliq; Muhammad Habib-ur-Rahman; Salma Niaz; Thomas Gaiser; Iqra Ghafoor; Hafiz Suboor ul Hassan; Muhammad Qasim; Gerrit Hoogenboom (Environmental Science and Pollution Research, 2022)
Future climate scenarios are predicting considerable threats to sustainable maize production in arid and semi-arid regions. These adverse impacts can be minimized by adopting modern agricultural tools to assess and develop successful adaptation practices. A multi-model approach (climate and crop) was used to assess the impacts and uncertainties of climate change on maize crop. An extensive field study was conducted to explore the temporal thermal variations on maize hybrids grown at farmer’s fields for ten sowing dates during two consecutive growing years. Data about phenology, morphology, biomass development, and yield were recorded by adopting standard procedures and protocols. The CSM-CERES, APSIM, and CSM-IXIM-Maize models were calibrated and evaluated. Five GCMs among 29 were selected based on classification into different groups and uncertainty to predict climatic changes in the future. The results predicted that there would be a rise in temperature (1.57–3.29 °C) during the maize growing season in five General Circulation Models (GCMs) by using RCP 8.5 scenarios for the mid-century (2040–2069) as compared with the baseline (1980–2015). The CERES-Maize and APSIM-Maize model showed lower root mean square error values (2.78 and 5.41), higher d -index (0.85 and 0.87) along reliable R 2 (0.89 and 0.89), respectively for days to anthesis and maturity, while the CSM-IXIM-Maize model performed well for growth parameters (leaf area index, total dry matter) and yield with reasonably good statistical indices. The CSM-IXIM-Maize model performed well for all hybrids during both years whereas climate models, NorESM1-M and IPSL-CM5A-MR, showed less uncertain results for climate change impacts. Maize models along GCMs predicted a reduction in yield (8–55%) than baseline. Maize crop may face a high yield decline that could be overcome by modifying the sowing dates and fertilizer (fertigation) and heat and drought-tolerant hybrids.

Economic study on biohydrogen production from liquid pineapple waste - Syaza I. Ahmad; Roslina Rashid; Zanariah Hashim; Chew Chee Meng; Chong Kar Lun; Den Muhammad Hamdi Jumaatuden; Norhidayah Ahmad Yasin; Ashella Jati; Mimi H. Hassim (Clean Technologies and Environmental Policy, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

Correction to: Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Environmental quality, forestation, and health expenditure: a cross-country evidence - Muhammad Awais Anwar; Ghulam Rasool Madni; Iftikhar Yasin (Environment, Development and Sustainability, 2021)

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies - Muhammad Safdar; Muhammad Sajjad Khan; Abdulkarim Yasin Karim; Shwan Ali Omar; Shukur Wasman Smail; Muhammad Saeed; Sana Zaheer; Mazhar Ali; Bilal Ahmad; Muhammad Tasleem; Yasmeen Junejo (Mammalian Genome, 2021)

Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafiz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Salicylic Acid– and Ascorbic Acid–Induced Salt Tolerance in Mung bean (Vigna radiata (L.) Wilczek) Accompanied by Oxidative Defense Mechanisms - Maria Nawaz; Muhammad Yasin Ashraf; Ameer Khan; Fahim Nawaz (Journal of Soil Science and Plant Nutrition, 2021)

Foliar Manganese Supply Enhances Crop Productivity, Net Benefits, and Grain Manganese Accumulation in Direct-Seeded and Puddled Transplanted Rice - Usman Zulfiqar; Saddam Hussain; Muhammad Ishfaq; Nauman Ali; Muhammad Umair Yasin; Muhammad Arif Ali (Journal of Plant Growth Regulation, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Growth and physio-biochemical responses of maize ( Zea mays L.) to drought and heat stresses - Madiha Ayub; Muhammad Yasin Ashraf; Abida Kausar; Salman Saleem; Sumera Anwar; Volkan Altay; Munir Ozturk (Plant Biosystems, 2021)

The impact of financial development, political institutions, and urbanization on environmental degradation: evidence from 59 less-developed economies - Iftikhar Yasin; Nawaz Ahmad; Muhammad Aslam Chaudhary (Environment, Development and Sustainability, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Relationship between adaptation to climate change and provincial government expenditure in Pakistan - Khuda Bakhsh; Aasma Latif; Rafaqet Ali; Muhammad Asim Yasin (Environmental Science and Pollution Research, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Impact of better cotton initiative on health cost and pesticide exposure of women cotton pickers in Punjab, Pakistan - Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Hafiz Irshad Hussain (Environmental Science and Pollution Research, 2021)

Climate change–induced human conflicts and economic costs in Pakistani Punjab - Khuda Bakhsh; Karim Abbas; Sarfraz Hassan; Muhammad Asim Yasin; Rafaqet Ali; Najid Ahmad; Muhammad Waqas Alam Chattha (Environmental Science and Pollution Research, 2020)

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Fazli Bari; Mohammad Haroon; Hazir Rahman; Nusrat Yasin; Taj Ali Khan; Mubbashir Hussain; Waheed Ullah (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Shigella flexneri: an emerging pathogen - Iqbal Nisa; Muhammad Qasim; Nusrat Yasin; Rafi Ullah; Anwar Ali (Folia Microbiologica, 2020)

Selective and simultaneous detection of cadmium, lead and copper by tapioca-derived carbon dot–modified electrode - Musa Yahaya Pudza; Zurina Zainal Abidin; Suraya Abdul-Rashid; Faizah Md Yasin; Ahmad Shukri Muhammad Noor; Jaafar Abdullah (Environmental Science and Pollution Research, 2020)

Bioethanol Mill Wastewater Purification by Combination of Coagulation-Flocculation and Microbial Treatment of Trametes versicolor INACC F200 - Ajeng Arum Sari; Tony Hadibarata; Ummu Hanifah; Ahmad Randy; Feni Amriani; Puspa Dewi N. Lotulung; Hasbi Yasin; Asep Saefumillah; Muhammad Ilyas (Water, Air, & Soil Pollution, 2019)

Correction to: Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Environmental and economic impacts of better cotton: a panel data analysis - Sundas Zulfiquar; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Samiullah; Saad Munir (Environmental Science and Pollution Research, 2019)

Ni tolerance and its distinguished amelioration by chelating agents is reflected in root radius of B. napus cultivars - Humera Nawaz; Stephan Manhalter; Aamir Ali; Muhammad Yasin Ashraf; Ingeborg Lang (Protoplasma, 2019)

Effect of exogenous nitric oxide on sulfur and nitrate assimilation pathway enzymes in maize (Zea mays L.) under drought stress - Sadia Majeed; Fahim Nawaz; Muhammad Naeem; Muhammad Yasin Ashraf (Acta Physiologiae Plantarum, 2018)

Exogenously applied zinc and copper mitigate salinity effect in maize (Zea mays L.) by improving key physiological and biochemical attributes - Muhammad Naveed Iqbal; Rizwan Rasheed; Muhammad Yasin Ashraf; Muhammad Arslan Ashraf; Iqbal Hussain (Environmental Science and Pollution Research, 2018)

Determination of groundwater potential by using geoelectrical method and petrographic analysis in Rawalakot and adjacent areas of Azad Kashmir, sub-Himalayas, Pakistan - Abrar Niaz; Muhammad Rustam Khan; Umer Ijaz; Muhammad Yasin; Fahad Hameed (Arabian Journal of Geosciences, 2018)

Kinetics, isotherms, and thermodynamic studies of lead, chromium, and cadmium bio-adsorption from aqueous solution onto Picea smithiana sawdust - Muhammad Mahmood-ul-Hassan; Muhammad Yasin; Munazza Yousra; Rizwan Ahmad; Sair Sarwar (Environmental Science and Pollution Research, 2018)

Terbufos sulfone aggravates kidney damage in STZ-induced diabetic rats - Syed Muhammad Nurulain; Shreesh Ojha; Mohamed Shafiullah; Javed Yasin; Tayyaba Yasmin; Tariq Saeed; Ernest Adeghate (Biologia, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Effect of reduced oxygen concentration on the germination behavior of vegetable seeds - Muhammad Yasin; Christian Andreasen (Horticulture, Environment, and Biotechnology, 2016)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Removal of Cd, Cr, and Pb from aqueous solution by unmodified and modified agricultural wastes - Muhammad Mahmood-ul-Hassan; Vishandas Suthor; Ejaz Rafique; Muhammad Yasin (Environmental Monitoring and Assessment, 2015)

Seleniferous soils as a source for production of selenium-enriched foods and potential of bacteria to enhance plant selenium uptake - Muhammad Yasin; Ali F. El Mehdawi; Courtney E. Jahn; Aneela Anwar; Marie F. S. Turner; Muhammad Faisal; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2015)

Effects of interactions among Metarhizium anisopliae, Bacillus thuringiensis and chlorantraniliprole on the mortality and pupation of six geographically distinct Helicoverpa armigera field populations - Waqas Wakil; M. Usman Ghazanfar; Tahira Riasat; Mirza Abdul Qayyum; Sohail Ahmed; Muhammad Yasin (Phytoparasitica, 2013)

Toxic Effect of Nickel (Ni) on Growth and Metabolism in Germinating Seeds of Sunflower (Helianthus annuus L.) - Muhammad Yasin Ashraf; Rumana Sadiq; Mumtaz Hussain; Muhammad Ashraf; M. Sajid Aqeel Ahmad (Biological Trace Element Research, 2011)

Studies on the chemical constituents of Phyllanthus emblica - Habib-ur-Rehman; Khawaja Ansar Yasin; Muhammad Aziz Choudhary; Naeem Khaliq; Atta-ur-Rahman; Muhammad Iqbal Choudhary; Shahid Malik (Natural Product Research, 2007)